Peran Kepemimpinan Pendidikan dalam Mengembangkan Keterampilan Kewirausahaan pada Siswa (International Forum of Researchers and Lecturers, 2024)
The role of educational leadership is very important in developing entrepreneurial skills in students, especially in the era of globalization that requires graduates to have independent and innovative abilities. Educational leadership acts as a catalyst in creating a conducive learning environment, facilitating an entrepreneurship-based curriculum, and integrating entrepreneurship programs into the learning process. This study aims to explore the role of educational leadership in developing entrepreneurial skills in students. Educational leadership has an important role in shaping students' character and skills, including entrepreneurial skills. The research method used is a literature study to collect data and information relevant to the research topic. The results of the study indicate that effective educational leadership can provide encouragement and motivation to students to develop their entrepreneurial skills. The implication of this study is the need for an active role of educational leadership in creating a learning environment that supports the development of entrepreneurial skills in students.